Analisis Payability Ratio dan Profitability dalam Penilaian Kinerja Keuangan : (Studi pada Perusahaan Daerah Air Minum (PDAM) Kota Makassar) - Anwar Anwar (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study expects solvency and profitability factors to be considered to understand the financial performance of the Makassar Regional Water Company (PDAM) from 2020 to 2024. This type of research is descriptive and quantitative. The city part of this study is the Financial Complaint of PDAM Makassar for the fifth period (2020-2024). The representative part of this audit is the judges and complaints related to the performance of Damas PDAM Makassar City for the 5th period (2020-2024). The information collection technique used in this audit is part-time documentation and the description of the information used in this audit is the details of solvency and profitability. The results of the study show solvency below the Kutel standard, a company that lays off PDAM Makassar City workers before paying off debts classified by contract. DAR and DER have decreased from year to year, and we can see that DAR and DER are in the lower range than the company average during the period 2023-2024. Profitability analysis shows that the company's internal talent generates great benefits through the overall NPM commitment. On the other hand, seen from ROI and ROE, the company has not been able to utilize all of its product raw materials to achieve net profit.